2018
DOI: 10.1007/s11596-018-1925-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of OAS2 rs739901 C/A Involves the Susceptibility to EV71 Infection in Chinese Children

Abstract: This study aimed to assess the relationship of OAS2 rs739901 5,-flanking C/A polymorphisms with the susceptibility to Enterovirus-71 (EV71) infection. We investigated 294 hand-foot-mouth disease (HFMD) Chinese children with EV71 infection (165 mild cases and 129 encephalitis cases). The improved multiplex ligation detection reaction (iMLDR) technique was used to test the genotypes. In EV71-infected patients, the CA genotype distribution (P=0.007), A allele frequency (OR 1.32,95% CI 1.0-1.7, P=0.034) and CA+AA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study showed that rs11574129 AA genotype and rs739837 GG genotype of vitamin D receptor ( VDR ) gene could reduce the risk of severe EV‐A71‐associated HFMD in Chinese children, accompanied by low serum vitamin D levels 13 . Tan et al 14 suggested that OAS2 rs739901 C/A gene polymorphism was related to EV‐A71 susceptibility, and A allele might be a risk factor for EV‐A71 infection. Similarly, the frequency of rs1889570 TT genotype and T allele in severe cases and EV‐A71 encephalitis cases were significantly higher and when compared with CC genotype, the serum IL‐17F levels of TT and CT genotype were also significantly higher 15 …”
Section: Discussionmentioning
confidence: 99%
“…A study showed that rs11574129 AA genotype and rs739837 GG genotype of vitamin D receptor ( VDR ) gene could reduce the risk of severe EV‐A71‐associated HFMD in Chinese children, accompanied by low serum vitamin D levels 13 . Tan et al 14 suggested that OAS2 rs739901 C/A gene polymorphism was related to EV‐A71 susceptibility, and A allele might be a risk factor for EV‐A71 infection. Similarly, the frequency of rs1889570 TT genotype and T allele in severe cases and EV‐A71 encephalitis cases were significantly higher and when compared with CC genotype, the serum IL‐17F levels of TT and CT genotype were also significantly higher 15 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have mainly focused on exploring the relationship between EV71 infection and host immunity at the molecular level, and it has been found that human gene polymorphisms, such as those of CPT2, OAS2, and IL-17F, are related to infection susceptibility and severity. [5][6][7][8][9] The transmembrane protein 173 (TMEM173), also known as MPYS, mediates the interferon regulatory factor 3 (IRF3) activation (MITA), endoplasmic reticulum interferon stimulator (ERIS), stimulator of interferon genes (STING), and stimulator of interferon response cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) interactor 1 (STING1). Human TMEM173 is located on chromosome 5q31.2, contains eight exons, and encodes a transmembrane protein between the endoplasmic reticulum and Golgi in response to the presence of cytosolic dsDNA as well as an adaptor protein that mediates the production of type I interferon.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have mainly focused on exploring the relationship between EV71 infection and host immunity at the molecular level, and it has been found that human gene polymorphisms, such as those of CPT2 , OAS2 , and IL‐17F , are related to infection susceptibility and severity. 5 , 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%